Two regional organizations and two national governments adopt cross-scale climate risk management approaches - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CCAFS scientists worked together with 2 regional organizations (CAC, CRRH) and two governments (Guatemala, Honduras) within the SICA (Central American Integration System) to boost pro-active CRM. To achieve this, CCAFS scientists: (1)co-developed and scaled decision-support tools so that regional organizations and national governments better understand the expected climatic variability and its implications on farming systems; (2)enabled the cross-scale information management, involving the integration of decision-makers at national/local levels with regional-scale processes.